Approaches to Optimization of Oligonucleotide Synthesis during Manufacturing of Preparations for Gene Diagnostics of Particularly Dangerous Infectious Diseases - A. V. Stepanov; N. V. Mayorov; N. A. Osina; A. K. Nikiforov (Проблемы особо опасных инфекций, 2016)
Objective of the study is to investigate the impact of activator, oxidize, and unblocking solution on the quantitative yield of oligonucleotides during manufacturing of the test-system for Vibrio cholerae (ctxA+) DNA detection “GenChol”, using polymerase chain reaction.Materials and methods. The subject of the study is ctx2 and ctx3 primers, incorporated in the test-system “GenChol”. Utilized have been experimental formulations of solutions for unblocking, activator, and oxidizer and “standard” solutions, recommended by the manufacturer “BioSet” Ltd. Specific activity of the synthesized primers ctx2 and ctx3 has been evaluated on three different strains: V. cholerae 569B, M-1298, 158 and E. coli 12226 O-55. Bacterial suspension from the pathogen with final concentration of 1·103 – 1·101 m.c./ml has been produced. The DNA has been isolated applying nucleo-sorption in presence of guanidinium isothiocyanate.Results and conclusions. Demonstrated is the possibility of optimization of diagnostic preparation production via increment of oligonucleotide yield in the process of phosphoramide synthesis, due to application of 3% dichloroacetic acid in dichloromethane as unblocking solution and oxidizer – 0.1 M iodine in athetic acid and pyridine in the ratio of 1:9. Utilization of such reagents increases the yield of the end product (primers) by 6 and 95 %, respectively. Enhanced technology for oligonucleotide synthesis will provide for the reduction of costs, associated with expensive imported reagents and the raise in the numbers of gene-diagnostic preparations for the detection of particularly dangerous pathogens.